Effect of soil organic carbon on the quantification of jet-fuels in soil using partitioning tracer method - Rhee, Sungsu; Lee, Seunghak; Park, Junboum (ELSEVIER, 2010)
Partitioning tracer method has been studied as an effective technique for estimating the light nonaqueous-phase liquid (LNAPL) contamination in the subsurface. This study is for investigating the effect of soil organic contents on the LNAPL quantification using partitioning tracer method. The sorption characteristics of alcohol tracers to the soils having different organic carbon contents were evaluated by sorption isotherm experiments. In the column tests, the soils were contaminated with jet-fuel and the average saturations of residual jet-fuel were estimated by partitioning tracer method and compared with that by the volume measurement. The sorption results indicated that considerable amount of 4-methyl-2-pentanol and hexanol could be sorbed to the soils and the sorption amount of 2-ethyl-1-butanol was relatively smaller than those of the other alcohol tracers. The column experiments demonstrated that the accuracy of quantification for the jet-fuel by partitioning tracer method should decrease with increasing the soil organic carbon contents. However, the accuracy could be enhanced by considering the sorption of tracer to the soils, especially for the tracer of 2-ethyl-1-butanol. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: NONAQUEOUS PHASE LIQUID; PERFORMANCE ASSESSMENT; INTERFACIAL TRACERS; POROUS-MEDIA; SOURCE ZONE; TESTS; NAPL; TRANSPORT